Tasks used by teachers for fostering the translation in the teaching-learning process of the english language in the second year of baccalaureate students of Ing. Eduardo Pazmiño Barciona and Carmen Mora de Encalada high schools in pasaje city, during academic year 2013-2014. - Campas Angulo, Ingrid Stefanía (2015)
Nowadays, the execution of new educational models in order to succeed in the teaching of a second language is a very urgent matter. Similarly, it is widely known that changing the method of teaching demands not only an engagement among authorities and teachers but also keep in mind the student needs and many other aspects. Therefore, it is necessary a detailed research to the establishment of tasks for fostering the translation as a strategical pattern in the teaching-learning process of English language, that is why the current paper is divided in chapters, as described below: Chapter I argues why there are many shortcomings regarding learning of English language in students of second year of baccalaureate study At Carmen Mora High School and Ing. Eduardo Pazmiño High School, and identifies the current effects and potential impacts. Furthermore, objectives are determined and it is emphasized the importance of development of new tasks for fostering the translation in order to enhance the learning and certainly, rise in the quality teaching. Chapter II highlights the key terms for the right performance and comprehension of the paper. Here is also the historical background of the concerned institutions. Chapter III outlines the methodology to be used: variables, indicators and hypothesis are formulated. Along with that, it is identified the universe and sample size of people involved in the matter of this paper. Chapter IV involves presentation of scientific research outcomes. That is display of graphs and charts, analysis, interpretation, verification of hypothesis and the corresponding conclusions and recommendations. Chapter V deals with the proposal, description, resources required, chronogram and a discussion which makes clear in advance what will occur in the presentation to the authorities and English teachers.